2023
DOI: 10.1002/pbc.30186
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to medication adherence among adolescents and young adults with cancer

Abstract: Background Adherence promotion is a critical component of adolescent and young adult (AYA) cancer care, but predictors of nonadherence that could be targeted in intervention efforts remain largely unknown. The purpose of this multi‐site longitudinal observational study was to examine the relationship between barriers and medication adherence among AYAs with cancer. Procedure Sixty‐five AYAs (ages 15–24 years; mean age = 18.97 years, SD = 2.51; Mmean time since diagnosis = 1.42 years, SD = 1.95) with newly diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…In a recent study that assessed medication adherence among patients with hematologic malignancies, it was observed that only 25% of patients adhered to medications, and many patients discontinued therapy for more than 30 days. Several barriers to medication were identified, including provider, patient, treatment, and socioeconomic factors [ 43 ]. The barriers to medication adherence are depicted in Figure 2 .…”
Section: Reviewmentioning
confidence: 99%
“…In a recent study that assessed medication adherence among patients with hematologic malignancies, it was observed that only 25% of patients adhered to medications, and many patients discontinued therapy for more than 30 days. Several barriers to medication were identified, including provider, patient, treatment, and socioeconomic factors [ 43 ]. The barriers to medication adherence are depicted in Figure 2 .…”
Section: Reviewmentioning
confidence: 99%